1997
DOI: 10.1002/(sici)1096-9861(19970602)382:2<230::aid-cne7>3.0.co;2-4
|View full text |Cite
|
Sign up to set email alerts
|

Neuritic differentiation and synaptogenesis in serum-free neuronal cultures of the rat cerebral cortex

Abstract: To better understand the dynamics of the cellular processes involved in early neocortical development, we studied the neuritic differentiation and synaptogenesis of dispersed neurons grown in serum-free cultures under a wide variety of culture conditions. Microtubule-associated protein (MAP2), phosphorylated neurofilament (SMI 31) and synaptophysin immunocytochemistry was complemented with time-lapse studies. During the first week in vitro dissociated cortical neurons developed from roundish cells without proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
50
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 74 publications
(54 citation statements)
references
References 74 publications
4
50
0
Order By: Relevance
“…E xperimental manipulations were only performed on OB cultures after they had been 5 d in vitro. This "pre-experimental" culture time was essential to allow cells damaged by dissociation to perish and for surviving cells to form dendrites, axons, and synapses, which does not occur in cortical neuron cultures until 3-4 d in vitro (De Lima et al, 1997), and to recover electrophysiological responses to amino acids. Both IPSPs and EPSPs are observed in OB cultures at 5 d in vitro (Trombley and Westbrook, 1990;Trombley and Shepherd, 1992), indicating that OB cells at the "age" used in the present experiments are electrophysiologically competent and respond to excitatory amino acid stimulation.…”
Section: Olfactory Neuroepithelial Slice Explants Induce Th Expressiosupporting
confidence: 87%
“…E xperimental manipulations were only performed on OB cultures after they had been 5 d in vitro. This "pre-experimental" culture time was essential to allow cells damaged by dissociation to perish and for surviving cells to form dendrites, axons, and synapses, which does not occur in cortical neuron cultures until 3-4 d in vitro (De Lima et al, 1997), and to recover electrophysiological responses to amino acids. Both IPSPs and EPSPs are observed in OB cultures at 5 d in vitro (Trombley and Westbrook, 1990;Trombley and Shepherd, 1992), indicating that OB cells at the "age" used in the present experiments are electrophysiologically competent and respond to excitatory amino acid stimulation.…”
Section: Olfactory Neuroepithelial Slice Explants Induce Th Expressiosupporting
confidence: 87%
“…For our particular investigations it was of great importance to determine maturity in vitro since previous investigations have demonstrated that the neuronal response to injury is dependent on neuronal maturity (Chuckowree and Vickers, 2003;Blizzard et al, 2007). Development of primary murine cortical neurons in vitro occurs via a sequence of steps across a defined time-course, involving neurite outgrowth, polarization and elongation followed by loss of immaturity markers such as growth cone markers and localization of synaptic proteins in dendritic spines as an indication of mature synapses (Dotti et al, 1988;Dichter, 1978;Picken Bahrey and Moody, 2003;De Lima et al, 1997;King et al, 2006). Neuronal development in culture in this study was assessed by the use of morphological, synaptic and electrophysiological characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…In our culture system, neuritogenesis followed a well defined stereotyped program: stage 1, within a few h (0 -2 h after changing to DM) of neuritogenesis, most cells started sprouting but were devoid of neurites; stage 2, within 2-4 h of neuritogenesis, neurons developed neurites and, depending on the number of neurites, cells' morphology could be divided into groups like unipolar, bipolar, and multipolar but none with established axon; stage 3, after 4 h of neuritogenesis, neurites started to grow and form axons, and the remaining neurites could not extend during this stage, consistent with a similar observation by de Lima et al (37). In control cells treated with nonspecific siRNA, we found that stage 1 and stage 2 were interchangeable Plasmid DNA containing GFP-tagged NMHC II-C isoform was transfected into 24-h post-siRNA-treated cells.…”
Section: Inhibition Of Nmhc Ii-c1c2 Interferes With a Late Stage Of Nmentioning
confidence: 99%